Sistema de control interno basado en el modelo coso, aplicado a la empresa bodegas y servicios Ecuador fortaleza S.A Bosefo. - Portilla Narváez, Maritza Mishel (2016)
This degree work is mainly based on the absentos of a system of internal control in the company Bodegas Y Servicios Ecuador Fortaleza SA of the city of Tulcan becilise control processes developed by the company 15 also necessary that the system interaal control allows activities to be managed under the guidelines previcusly established parameltrs, ts achieving a recrganization in the roles within (be company. becanse allows tasks to be carried out efficiently and effectively generaling accurate ard reliable information in order that the institution right decisions to improve service and establish strategies focused on the fuifilMment of proposed goals and targets are taken The methodology used for this research work is based on empirical methods which allows us to analyze the current situation of the company in order to diagnose the problem that is raising in particular institution; Mheoretical methods in which the theoretical basis of the internal control system 16 investizaled, tus helping to interprel ihe information gathered and supporting development work: as well as implementing research techniques which allow us to obtain necessary and trothfal informatión for the present research work. AM with the sole purpose of establishing control operations performed by the company, achieving a practical model design and easy 1 undesstand the same 15 focused on the Coso model whieh consists of five components; Control environment which allows the company to develop lis activities under regulations and guidelines; Risk assessment identifes risk to analyze and verify the effective implementation of the objectives; Control activities are palicies and procedures that let you Jnow if the activities are developing eftectively and ás it establishes, Information and communication system which focuses 0n determining fluid communication al all levels of the company Establishing supervision añd monitoring controls that allow observe the effective implementation of the various operations which contribute to improve the eliicient fulfillmment of the tasks the company, $0 11 is advisable to apply the model of internal control system performed